2012
DOI: 10.2528/pierc12081902
|View full text |Cite
|
Sign up to set email alerts
|

A SRR-Based Near Field Rfid Antenna

Abstract: In this paper, a compact near field reader antenna is proposed for ultra-high frequency (UHF) radio frequency identification (RFID) applications. The antenna structure is composed of two split-ring-resonators (SRRs) and miniaturized to a special small size of 21 * 21 * 1.6 mm 3 for mobile RFID application. The measured bandwidth of antenna prototype is 13 MHz (914.5-927.5 MHz) with reflection coefficient less than −10 dB, which covers the China RFID band II (920-925 MHz). Simulation shows that the proposed ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…L is the equivalent inductance loading depends on the length of rings and C is the equivalent capacitance loading determined by the gap between the rings and the splits at each ring. Both capacities and inductive loading are simultaneously applied as an LC tank circuit, and resonance characteristic results an antenna size reduction …”
Section: Novel E‐shaped Split Ring Resonator Metamaterialsmentioning
confidence: 99%
“…L is the equivalent inductance loading depends on the length of rings and C is the equivalent capacitance loading determined by the gap between the rings and the splits at each ring. Both capacities and inductive loading are simultaneously applied as an LC tank circuit, and resonance characteristic results an antenna size reduction …”
Section: Novel E‐shaped Split Ring Resonator Metamaterialsmentioning
confidence: 99%
“…The assessment of the proposed fractal antenna with other existing fractal antennas is tabulated in Table 3. From Table 3, it can be observed that the antennas designed in [22,23,[28][29][30] are compact in size as compared to the proposed fractal antenna. However, these antennas have less frequency bands and bandwidth than the proposed fractal antenna.…”
Section: Prototype and Resultsmentioning
confidence: 99%
“…An SRR based compact near-field antenna was reported [23] by some researchers for RFID applications. Through modifying the parameters of SRRs, researchers miniaturized the size of the antenna and operated on different UHF RFID bands.…”
Section: Introductionmentioning
confidence: 99%